Hold me closer : the Tiny Cooper story - Levithan, David (2015)
"Larger-than-life Tiny Cooper finally gets to tell his story, from his fabulous birth and childhood to his quest for true love and his infamous parade of ex-boyfriends, in the form of a musical he wrote"--
Companion book to: Will Grayson, Will Grayson by John Green and David Levithan.
"A musical in novel form (Or, a novel in musical form)."
Keywords: Gays -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Musicals -- Juvenile fiction